Glycolate: Dichlorophenolindophenol Oxidoreductase in Chlamydomonas reinhardtii - Cooksey, Keith E. (Plant Physiol, 1971)
Glycolate: dichlorophenolindophenol oxidoreductase levels in Chlamydomonas reinhardtii are not under the immediate control of the CO(2) tension to which the cells are exposed. The enzyme is synthesized initially in 5% CO(2) in air at a similar rate to that in air. It disappears from the cell under nitrogen-limitation.